WEB SITE DESIGN BY ORGANIZATION FORMASI USINGMACROMEDIA DREAMWEAVER 8.0 - Rahmat Hidayat (Jurnal Manajemen Informatika, 2010)
The rapid development of the computer becomes a facilitator to obtaininformation easily without having to spend a huge cost. The presence of the Internet hasbrought the information revolution. Through this network of information flow so swiftflowing across national borders. By exploiting and using the Internet, users worldwidecan communicate and use shared information. In addition, the Internet also can be usedas ameans of promotion.Therefore, the authors want to promote the website which the author created with thetitle â€œ Website Design By Organization Formasi Using Macromedia Dreamweaver 8.0.â€in which this website provides information about the Islamic world that is being developedat this time through events or information made by this organization .